A Brief Understanding of Medieval Indian University Education System: A Review - Parth M Lakum; Rishabh D Makwana; Mayur R Chotaliya; Darshan H Bhalodiya (International Journal of Trends in Humanities, 2024)
Any Nation’s progress and future can be forecasted by taking a glance at their education system. Modern education system is no doubtedly high in technology and methodology, but the morals and ethical importance might be lacking. According to renowned Takshshila University professor Chanakya, a teacher is not your typical individual; they live in a world of constant development and destruction. He attended one of the venerable universities in lovely India as a student and later as a professor. We recognize many profound universities around the world in modern era such as Oxford or Cambridge. These universities have been spreading knowledge for decades. In medieval India the education system included universities such as Takshashila, Nalanda, Vallabhi Vidhyapith. These Institutions attracted scholars, learners, pupils and researchers from all over the world. Indian subcontinent was thriving with rich knowledge, research and information that attracted visitors from far out lands such as Fa Hein and Huan Tsang. These visitors stayed and gathered knowledge regarding Buddhism and Hinduism which they translated in to Tibetic and Mandarin Languages. Irony is that the original manuscript in Brahmi, Pali, Prakrit and Sanskrit are no longer available but their translations from Tibet or Persia are available in parts. The universities have been vandalized or destroyed and the knowledge is lost in the archives of time. To understand the ancient Indic culture we have to be depended on these foreigners who valued Indian education system and documented it. This paper is a modest attempt to provide insight into the development and collapse of the Indian education system in the Middle Ages.
Keywords: Indic Education System; Medieval India; Nalanda; Roots of Indian Universities; Takshashila